Long‐term human IgG treatment improves heart and muscle function in a mouse model of Duchenne muscular dystrophy. Issue 4 (20th May 2020) - Zschüntzsch, Jana; Jouvenal, Pia Vanessa; Zhang, Yaxin; Klinker, Florian; Tiburcy, Malte; Liebetanz, David; Malzahn, Dörthe; Brinkmeier, Heinrich; Schmidt, Jens
Abstract: Background: Duchenne muscular dystrophy (DMD) is a progressive muscle‐wasting disease caused by mutations in the dystrophin gene, which leads to structural instability of the dystrophin–glycoprotein‐complex with subsequent muscle degeneration. In addition, muscle inflammation has been implicated in disease progression and therapeutically addressed with glucocorticosteroids. These have numerous adverse effects. Treatment with human immunoglobulin G (IgG) improved clinical and para‐clinical parameters in the early disease phase in the well‐established mdx mouse model. The aim of the present study was to confirm the efficacy of IgG in a long‐term pre‐clinical study in mdx mice. Methods: IgG (2 g/kg body weight) or NaCl solution as control was administered monthly over 18 months by intraperitoneal injection in mdx mice beginning at 3 weeks of age. Several clinical outcome measures including endurance, muscle strength, and echocardiography were assessed. After 18 months, the animals were sacrificed, blood was collected for analysis, and muscle samples were obtained for ex vivo muscle contraction tests, quantitative PCR, and histology. Results: IgG significantly improved the daily voluntary running performance (1.9 m more total daily running distance, P < 0.0001) and slowed the decrease in grip strength by 0.1 mN, ( P = 0.018). IgG reduced fatigability of the diaphragm (improved ratio to maximum force by 0.09 ± 0.04, P = 0.044), but specific tetanic force remained unchanged in the ex vivo muscle contraction test. Cardiac function was significantly better after IgG, especially fractional area shortening ( P = 0.012). These results were accompanied by a reduction in cardiac fibrosis and the infiltration of T cells ( P = 0.0002) and macrophages ( P = 0.0027). In addition, treatment with IgG resulted in a significant reduction of the infiltration of T cells ( P ≤ 0.036) in the diaphragm, gastrocnemius, quadriceps, and a similar trend in tibialis anterior and macrophages ( P ≤ 0.045) in gastrocnemius, quadriceps, tibialis anterior, and a similar trend in the diaphragm, as well as a decrease in myopathic changes as reflected by a reduced central nuclear index in the diaphragm, tibialis anterior, and quadriceps ( P ≤ 0.002 in all). Conclusions: The present study underscores the importance of an inflammatory contribution to the disease progression of DMD. The data demonstrate the long‐term efficacy of IgG in the mdx mouse. IgG is well tolerated by humans and could preferentially complement gene therapy in DMD. The data call for a clinical trial with IgG in DMD.